Low-Cost Germicidal UV LED as Candidate Light Source for Portable and Field Spectrometer. Issue 1 (June 2021) - Sakti, S P; Anggraeni, D; Putro, T
Abstract: Ultraviolet Light Emitting Diode (UV LED) is becoming popular, especially during the Covid-19 pandemic. UV LED has a specific wavelength with relatively narrow bandwidth, especially the one that has a shorter wavelength. On the other hand, UV LED has advantages in its low power consumption, compact size, and longer lifetime. This work shows that a wider bandwidth can be elicited by combining multiple UV LED sources. We have measured several low-cost UV LED, which is used as a germicidal lamp using a portable spectrometer that can detect a wavelength from 200 nm to 850 nm. The combined UV LED spectrum light ranges from 254 nm UVC to 400 nm UVA. The light spectrum produced by the LED shows a form of the Gaussian distribution model. Some LEDs have a peak wavelength at UVC around 270nm, and LEDs have a peak wavelength around 400nm at UVA. We can conclude that the low-cost UV LED can be used as a light source for portable or field spectrometers for specific wavelength.